Old-fashioned antithrombotic drugs: will they be sent to a museum? - Argumanis Sánchez, Luis Enrique G. (2022)
The development and prescription of drugs that alter the hemostatic balance marked an important breakthrough in the treatment and prevention of thromboembolic events, which has drastically reduced the associated morbidity and mortality. The discovery of heparin and coumarin anticoagulants, as well as the description of their thrombotic activities, opened a new therapeutic scenario.